Safety and efficacy of an extended‐release peptide YY analogue for obesity: A randomized, placebo‐controlled, phase 1 trial. Issue 7 (9th March 2021) - Tan, Tricia M.‐M.; Minnion, James; Khoo, Bernard; Ball, Laura‐Jayne; Malviya, Reshma; Day, Emily; Fiorentino, Francesca; Brindley, Charlie; Bush, Jim; Bloom, Stephen R.
Abstract: Aim: To report the results from a Phase 1 trial of an extended‐release peptide YY analogue, Y14, developed for the treatment of obesity. Methods: Y14 was evaluated in overweight/obese volunteers in a Phase 1 randomized placebo‐controlled trial, conducted in a clinical trial unit in the United Kingdom. Part A was a blinded single‐ascending‐dose study evaluating doses up to 36 mg. Part B was double‐blinded and tested multiple ascending doses between 9 and 36 mg, given at 7‐ to 14‐day intervals, over the course of 28 days, with up to five doses given per participant. The primary outcome was safety and tolerability; the secondary outcome was assessment of pharmacokinetic (PK) characteristics. Exploratory outcomes included food intake, body weight change and glucose tolerance after multiple doses. Results: Between April 11, 2017 and December 24, 2018, 53 participants were enrolled into Part A and 24 into Part B of the trial. The PK characteristics were compatible with administration every 7 to 14 days. The most common adverse events (AEs) were nausea, vomiting or administration site reactions, which were mild in most cases and settled with time. No serious AE occurred. Participants given multiple doses of Y14 lost between −2.87 and −3.58 kg body weight compared with placebo ( P  <0.0001) at 31 days from the first dose, with profound reductions in food intake of 38% to 55% ( P  <0.0001, compared to placebo) and there was no evidence of tachyphylaxis. Conclusions: Our results support the continued development of Y14 as a novel treatment for obesity.